Midterm and one-year outcome of amphilimus polymer free drug eluting stent in patients needing short dual antiplatelet therapy. Insight from the ASTUTE registry (AmphilimuS iTalian mUlticenTer rEgistry). (15th March 2017) - Godino, Cosmo; Chiarito, Mauro; Donahue, Michael; Testa, Luca; Colantonio, Riccardo; Cappelletti, Alberto; Monello, Alberto; Magni, Valeria; Milazzo, Diego; Parisi, Rosario; Nicolino, Annamaria; Moshiri, Shahram; et al.
Abstract: Background: To assess clinical outcomes of patients needing short dual antiplatelet therapy (S-DAPT) after PCI with Cre8 polymer-free amphilimus eluting-stent (AES). The Cre8-AES with pure i-Carbofilm coating was supposed to induce faster stent endothelialization and reduce device thrombogenicity. Methods: We performed a sub-analysis of unrestricted consecutive patients treated with Cre8-AES between August 2011 and January 2015. Two groups were formed: 1) patients discharged with S-DAPT (≤ 3-month), because of high bleeding risk or attending urgent non-cardiac surgery; and 2) patients discharged with Recommended DAPT duration (R-DAPT; ≥ 6-month). The primary ischemic- and bleeding-safety endpoints were Target Vessel Failure (TVF, composite endpoint of cardiac-death, target vessel-myocardial infarction and target vessel-revascularization), and major-bleeding (BARC ≥ type-3a) at 6-month and 1-year. Results: 106 patients (8.7%) were discharged with ≤ 3-month DAPT (83 ± 19 days; S-DAPT group) and 1102 patients (90.6%) with ≥ 6-month DAPT (342 ± 62 days; R-DAPT group). Between S-DAPT and R-DAPT groups no significant differences were observed in TVF at 1-year (5.7% vs 5.1%); 1-year BARC major bleeding rate was higher in S-DAPT group (3.4% vs 0.2%, p  = 0.007) with all bleeding events occurred within 3 months. The landmark analysis (started at 90 days, ended at 1 year) showed no differences in BARC major bleedings between groups (0% vs. 0.3%). Conclusions: The results of this multicenter registry show that the use of Cre8 AES in patients needing short DAPT (≤ 3-month) was safe regarding ischemic events and could favor a reduction of bleeding events related to the recommended DAPT. A large randomized trial is necessary to support these preliminary findings.